2019
DOI: 10.1039/c9dt00068b
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Bi3TaO7–Bi4TaO8Br composites in ambient air and their high photocatalytic activity upon metal loading

Abstract: Cocatalyst loading on ambient-air synthesized Bi3TaO7–Bi4TaO8X (X = Cl, Br) composites for highly suppressed exciton recombination and efficient solar light harvesting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 40 publications
0
14
0
Order By: Relevance
“…As for enhancing the photocatalytic activity of Bi 4 TaO 8 Cl, the primary challenges are promoting the carrier separation and building more reaction sites to accelerate the kinetic reaction rate. At present, several tactics have been proposed and implemented, such as constructing heterojunctions, [15][16][17] modifying noble metals, [18][19][20] doping elements, [21][22][23][24][25][26] and facet engineering, 14,[27][28][29][30][31] etc. Chen's group reported that the synthesis of a rutile TiO 2 heterojunction exposed different crystal facets and they proved that the formed facet heterojunction played a key role in charge separation.…”
Section: Introductionmentioning
confidence: 99%
“…As for enhancing the photocatalytic activity of Bi 4 TaO 8 Cl, the primary challenges are promoting the carrier separation and building more reaction sites to accelerate the kinetic reaction rate. At present, several tactics have been proposed and implemented, such as constructing heterojunctions, [15][16][17] modifying noble metals, [18][19][20] doping elements, [21][22][23][24][25][26] and facet engineering, 14,[27][28][29][30][31] etc. Chen's group reported that the synthesis of a rutile TiO 2 heterojunction exposed different crystal facets and they proved that the formed facet heterojunction played a key role in charge separation.…”
Section: Introductionmentioning
confidence: 99%
“…Bismuth oxyhalides of the type Bi 2p orbitals rather than X np orbitals. 13,14 This feature leads to photostability, while these materials are still visible light absorbing. 15 The understanding of such a unique electronic structure is still not fully clear because of their structural complexity arising from the tilting of perovskite MO 6 octahedra, giving rise to independent O sites for Bi 4 MO 8 X.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Bismuth oxyhalides of the type Bi 4 MO 8 X (M = Nb and Ta; X = Cl and Br) or Bi 2 AO 4 X (A = most Ln; X = Cl, Br, and I) have a unique electronic band structure near the VBE compared to BiOX, where the major contribution is from O 2p orbitals rather than X np orbitals. , This feature leads to photostability, while these materials are still visible light absorbing . The understanding of such a unique electronic structure is still not fully clear because of their structural complexity arising from the tilting of perovskite MO 6 octahedra, giving rise to independent O sites for Bi 4 MO 8 X.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, metal oxyhalides of the type Bi 4 MO 8 X (M = Ta, Nb; X = Cl, Br) have shown potential as durable photocatalysts with visible-light irradiation. Bi 4 MO 8 X materials are layered Sillén-Aurivillius perovskites whose structure is composed of Sillén blocks (alternating [Bi 2 O 2 ] +2 , X – slabs) and Aurivillius blocks (alternating [Bi 2 O 2 ] +2 [MO 4 ] −3 slabs) . Density of states (DOS) calculated for Bi 4 MO 8 X indicate that the VBM are composed of Bi 6s and O 2p orbitals while the nonoxide halogen orbitals contribute to lower energy states in the valence band (similar to Figure c rather than Figure b) .…”
Section: Metal Oxyhalidesmentioning
confidence: 99%